Compilation of Alumni Profiles Based on Tracker Study in the Doctoral Study Program (S3) of Postgraduate Education, State University of Gorontalo - Novianty Djafri; Syamsu Qamar Badu; Imam Mashudi (Asosiasi Profesi Multimedia Indonesia, 2023)
The Doctor of Education Program at State University of Gorontalo will carry out the accreditation, where the alumni's track record and user satisfaction have a sizable portion in the accreditation assessment. This service aims to identify, record, formulate and analyze the profiles of graduate students based on tracer studies in the postgraduate doctoral study program, State University of Gorontalo. In particular, this study aims to: 1) Describe tracer study-based student and alumni profiles in the Postgraduate Education Doctoral Study Program, State University of Gorontalo; 2) Mapping the curriculum in the Postgraduate Education Doctoral Study Program, State University of Gorontalo. This service is designed using a mix method with data collection techniques using questionnaires, observation, interviews, and documentation. Data analysis techniques using quantitative analysis and qualitative analysis. This service is expected to: a) be input or reference material in improving the quality of students and alumni in the Doctoral Study Program of Postgraduate Education, State University of Gorontalo, b) become a reference in carrying out study and postgraduate program policies in developing the vision and mission of the organization, c) be a reference in the development of study programs and postgraduate programs in preparing accreditation forms in the future, and d) be useful for the formulation of work programs for the Doctor of Education Study Program that are more responsive to the needs of students and alumni. The end result of this service is expected to be; 1) Formulate a Compilation of Profiles of Doctoral Education Graduates for Users of Postgraduate Education Doctoral Graduates, State University of Gorontalo, and also 2) a Compilation of the Curriculum for the Doctoral Study Program in Postgraduate Education, State University of Gorontalo, with the Outcomes of the Collaborative Service Program being; 1) Consolidated Service Report Formulation of Doctoral Education Graduate Profiles and Doctoral Education Curriculum for Users of Doctoral Graduates (S3) in Postgraduate Education, State University of Gorontalo. 2) Service Journal. 3) Publication of Service Activities in Gorontalo Post or Electronic Print Media; Instagram and FB. 4) IPR Grand Design Service Research Report Based on Tracer Study at the Doctoral Study Program of Postgraduate Education, State University of Gorontalo.